YOUTH EMPOWERMENT THROUGH CHARACTER EDUCATION IN FACING CHANGE SOCIAL - Tamimi, Muhammad; Raman, Raman (LPPM Universitas Bina Bangsa, 2025)
Generation Z teenagers often face emotional pressure that comes from various sources, such as academic stress, social interactions, and societal demands. This has the potential to cause mental health problems, including anxiety and depression. This article aims to provide an up-to-date analysis of character management and emotional regulation relevant to Generation Z, with an emphasis on high moral and ethical values. Implementing strategies such as emotional education, wise use of technology, adequate access to mental health services, and creating a supportive environment is very important. Apart from that, parental involvement, training for teachers, and participation in extracurricular activities are also crucial factors. Collaborative efforts from all stakeholders are needed to create an environment that can support positive growth for Generation Z. Character education management is key in ensuring their mental and emotional well-being. By understanding the challenges, they face and implementing the right strategies, we can help Generation Z develop the skills needed to deal with pressure and become healthy, competitive individuals in the digital era.